Postoperative chemoradiotherapy in patients with head and neck cancer aged 70 or older with positive margins or extranodal extension and the influence of nodal classification. Issue 6 (8th February 2018) - Yoshida, Emi J.; Luu, Michael; David, John M.; Kim, Sungjin; Mita, Alain; Scher, Kevin; Shiao, Stephen L.; Tighiouart, Mourad; Ho, Allen S.; Zumsteg, Zachary S.
Abstract: Background: Postoperative concomitant chemoradiotherapy (CRT) improves outcomes for younger adults with head and neck squamous cell carcinoma (HNSCC) and positive margins or extranodal extension (ENE), but its benefit for older adults is not well established. Methods: Patients from the National Cancer Data Base (NCDB) with HNSCC undergoing curative‐intent resection, neck dissection, and postoperative radiation with positive margins or ENE were identified. Results: This analysis included 1199 patients aged ≥ 70 years with median follow‐up of 42.6 months. Postoperative concurrent CRT was associated with improved overall survival (OS; hazard ratio [HR] 0.752; 95% confidence interval [CI] 0.638‐0.886) compared to radiation alone in multivariable analysis. Three‐year OS was 52.4% with CRT versus 43.4% with radiation ( P  = .012) in propensity‐score matched cohorts. The survival impact of CRT varied by N classification ( P  = .002 for interaction), with benefit seen only in those with N2 to N3 disease. Conclusion: Postoperative concurrent CRT may benefit older patients with HNSCC with positive margins or ENE, particularly those with higher nodal burden.